2019
DOI: 10.1016/j.rmed.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Beyond inspiratory muscle strength: Clinical utility of single-breath work capacity assessment in veterans with COPD

Abstract: Background: Inspiratory muscle function in COPD has been traditionally described in terms of maximal inspiratory pressure (MIP). Arguably, however, is the day-to-day relevance of MIP, given that individuals rarely need maximal inspiratory forces to perform general tasks, but rather repeated breathing muscle contractions which demand endurance. The sustained maximal inspiratory pressure (SMIP) reflects the ability of the respiratory muscles to maintain force over time (i.e. single-breath work capacity). We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…MIP, the greatest pressure generated in the first two seconds of an inspiratory maneuver, reflected inspiratory muscle strength [ 36 , 37 ]. SMIP, the pressure generated from residual volume (RV) to total lung capacity (TLC), reflected the ability of inspiratory muscles to maintain pressure over time [ 38 40 ]. ID measures the time of maximal inspiratory effort [ 38 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…MIP, the greatest pressure generated in the first two seconds of an inspiratory maneuver, reflected inspiratory muscle strength [ 36 , 37 ]. SMIP, the pressure generated from residual volume (RV) to total lung capacity (TLC), reflected the ability of inspiratory muscles to maintain pressure over time [ 38 40 ]. ID measures the time of maximal inspiratory effort [ 38 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…While MIP has been extensively studied in SCI and other populations, SMIP is a newer measure of respiratory health. Fromiga et al reported a stronger relationship among SMIP, lung function, and symptom severity than with MIP in a sample of veterans with COPD [37]. In addition, SMIP was a more sensitive and specific predictor for successful extubation outcome than MIP, further linking lung function and SMIP [38].…”
Section: Discussionmentioning
confidence: 95%
“…22 Based on data regarding the correlation between SMIP and MIP in a COPD cohort, this corresponds to an SMIP value of 427 pressure time unit (PTU). 20 Therefore, a combined MIP < 80 cmH 2 O and SMIP < 427 PTU was used to define inspiratory muscle weakness. Subjects were not eligible to participate if they were actively undergoing pulmonary rehabilitation, unable to perform the required procedures for testing inspiratory muscle weakness (e.g., tracheostomy), or not clinically stable (i.e., current exacerbation or one within the past 4 weeks).…”
Section: Methodsmentioning
confidence: 99%
“…These measures, along with MIP, are assessed using the Test of Incremental Respiratory Endurance (TIRE), which has recently been shown to provide greater clinical relevance when examining respiratory performance in COPD, as it assesses not only inspiratory muscle strength but endurance as well. 20 The clinical utility of the TIRE outcome measures appears to be superior to MIP alone because TIRE captures all of the above measurements and has been shown to have excellent test-retest reliability and known-groups validity in subjects with COPD. 21 The primary purpose of this study was to investigate the effects of yoga training on IMP using the TIRE.…”
Section: Introductionmentioning
confidence: 99%